UJI SUN PROTECTION FACTOR (SPF) DAN AKTIVITAS PEREDAMAN RADIKAL BEBAS PADA HIDROSOL KAYU MANIS (Cinnamomum verum) - Dewi, Aptika Oktaviana; Aidah, Hana; Adisti, Arriyana Putri; Ifadah, Fais; Azzahro, Zulfa Citra (Jurnal Farmasindo: Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
Cinnamon hidrosol (Cinnamomum verum) is a byproduct of the distillation process that has potential as an antioxidant and sunscreen, but is still rarely utilized. This study aims to determine the phytochemical content, sunscreen activity (SPF), and antioxidant activity of cinnamon hidrosol. Hidrosol was obtained by distillation for 4 hours with a ratio of material and solvent 1:3.5. Phytochemical tests were carried out qualitatively, SPF activity testing was carried out using the UV-Vis spectrophotometry method, and antioxidant activity testing used the DPPH method. The results showed that hidrosol from the distillation flask contained alkaloids, saponins, and phenolics, while from the distillate flask contained flavonoids, alkaloids, and phytosterols. The SPF test results showed the highest value in the distillation flask hidrosol of 39.78 which is included in the ultra protection category. The results of the antioxidant activity test showed an increasing % inhibition with increasing concentration, with an IC₅₀ value of the distillation flask hidrosol of 310.77 µg/mL (very weak category). In conclusion, cinnamon hidrosol has potential as a natural sunscreen ingredient, despite its relatively weak antioxidant activity. Therefore, it can be used as an additive in cosmetic products.